Advancement of conventional cost benefit for selection of truly sustainable infrastructure alternatives - Kondrachova, T.; Grasselli, G.; Miller, E. (Expanding Underground - Knowledge and Passion to Make a Positive Impact on the World, 2023)
In the 21st century, selection of a best infrastructure alternative became prominent for all public sector projects. Initially, such selection was using the well-established for assessment of most profitable private investments, the cost-benefit approach. Criticized for insufficient inclusion of project social and ecological effects, this approach was later replaced with variety of multi-criteria-based methods. An overview of both approaches identifies their advantages and potential burdens for fair assessment of economical, social, and ecological effects. All analyses are supported by world-wide practical examples with emphasis on historical tunnelling projects from Greater Toronto (Canada). Relying on some findings by Canadian and Australian scholars and the results of their own research, the authors develop an enhancement to the conventional cost-benefit approach to ensure selection of fact-proven most sustainable alternatives. As demonstrated, application of this methodology can reduce infrastructure planning timeline, also working toward its better sustainability and helping with achievement of the United Nations' Sustainable Development Goals.